2003
DOI: 10.1144/gsl.sp.2001.211.01.14
|View full text |Cite
|
Sign up to set email alerts
|

GPR survey of a lobate rock glacier in Yankee Boy Basin, Colorado, USA

Abstract: The internal structure of a lobate rock glacier located in the San Juan Mountains of southwest Colorado was investigated using ground penetrating radar (GPR). A 440 m, 25 MHz longitudinal profile oriented along the central axis of the rock glacier shows moderate to strongly coherent reflection horizons or layers that can be recognized clearly to a depth of 30-35 m. The layers are interpreted as representing ice-supersaturated sediments and coarse, blocky rockslide debris that are the result of flow, perhaps ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 27 publications
8
35
0
Order By: Relevance
“…For example, 1) Straight and parallel reflectors concordant with a basal one express low longitudinal deformation and/or vertical compaction; 2) Chaotic reflectors may reflect local downwasting and perturbation of the shallow structure; 3) Undulating and toplapping reflectors; and 4) upward-or rock glacier center-dipping reflectors rather evocate the occurrence of compressive stresses and thrusting. Indeed, undulating and toplapping reflectors are well known in rock glacier deformation structures (e.g., Degenhardt et al, 2003;Monnier et al, 2008), and the dipping reflectors observed here are analogous to GPR signatures given by thrust planes in glaciotectonized sediments (Overgaard and Jakobsen, 2001;Sadura et al, 2005) or by debris inclusions in glacier ice (Woodward et al, 2003) and debris-covered glacier ice structures in rock glaciers (Fukui et al, 2008).…”
Section: Migrated and Automatic Gain Control (Agc)-enhanced Profiles:supporting
confidence: 64%
“…For example, 1) Straight and parallel reflectors concordant with a basal one express low longitudinal deformation and/or vertical compaction; 2) Chaotic reflectors may reflect local downwasting and perturbation of the shallow structure; 3) Undulating and toplapping reflectors; and 4) upward-or rock glacier center-dipping reflectors rather evocate the occurrence of compressive stresses and thrusting. Indeed, undulating and toplapping reflectors are well known in rock glacier deformation structures (e.g., Degenhardt et al, 2003;Monnier et al, 2008), and the dipping reflectors observed here are analogous to GPR signatures given by thrust planes in glaciotectonized sediments (Overgaard and Jakobsen, 2001;Sadura et al, 2005) or by debris inclusions in glacier ice (Woodward et al, 2003) and debris-covered glacier ice structures in rock glaciers (Fukui et al, 2008).…”
Section: Migrated and Automatic Gain Control (Agc)-enhanced Profiles:supporting
confidence: 64%
“…While penetration depth increases at low frequencies, the depth resolution decreases. Frequencies between 6.4 and 250 MHz have been used to measure thickness of up to about 40 m and internal properties of rock glaciers in the Alps, the polar regions, and the United States (Fukui et al, 2007;Degenhardt, 2009;Degenhardt et al, 2003;Nickus et al, 2015).…”
Section: Gprmentioning
confidence: 99%
“…Data collection typically involves centerpoint antenna frequencies of 25, 50, or 100 MHz (e.g., Isaksen et al, 2000;Degenhardt et al, 2003;Berthling et al, 2003). This range usually provides the best optimization between resolution and depth of penetration when antennas are used in broadside reflection mode with constant sourcereceiver offsets (Jol and Bristow, 2003).…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…9A). Given suitable magnitude, volumes and discharge frequency, debris lobes can coalesce or stack to form a "composite" rock glacier such as the one at Gilpin Peak (Degenhardt et al, 2003). In contrast, if debris is being supplied primarily from a narrow zone along the cirque wall over an extended period of time, a tongue-shaped rock glacier will likely result.…”
Section: Fundamental Controls On Gross Morphologymentioning
confidence: 99%